Milton Friedman: An early advocate of dollarization? - Emilio Ocampo (Universidad del Centro de Estudios Macroeconómicos de Argentina (UCEMA), 2022)
Milton Friedman's longstanding advocacy in favor of floating exchange rates has contributed to a mistaken belief that he opposed currency board regimes or outright dollarization. Nothing could be further from the truth. Over a period of almost five decades Friedman consistently made it clear that he favored floating exchange rates for advanced nations but not for developing nations. In fact, he was one of the earliest advocates of dollarization for countries suffering from high and chronic inflation such as Argentina. Interestingly, it is rarely known that one of the earliest debates on the advantages and disadvantages of dollarization and currency boards took place in 1973 in Washington, D.C., during a Congressional Hearing which pitted Friedman against Argentine economist Ricardo Arriazu. The purpose of this brief note is to trace the evolution of Friedman's thinking on the subject from the mid 1950s until his death and the events that influenced it.
Keywords: B2; B17; B3; B22; B27; F31; F32; O24; 330; Milton Friedman; Foreign Exchange Rate Regimes; Currency Boards; Dollarization; Monetary Policy; Argentina